Framing effects on time preferences: The impact of investment and loan contexts in intertemporal choices - Shohei Yamamoto; Shotarao Shiba (Osaka University, Institute of Social and Economic Research (ISER), 2024)
Our decisions frequently involve the combinations of gains and losses occurring at different points in time, such as enduring early losses for future gains (investments), or enjoying immediate gains at the expense of future losses (loans). This study introduces novel experiments that examine how binary intertemporal payment options, framed as either investments or loans, influence decision-making. Each option comprised two payment components: common payments, which are identical between the options, and main payments, which vary between the options. Through strategic manipulation of these payments, the study explores how investment or loan frames affect time preferences. Our studies consistently indicate that the common payments tend to be disregarded, thus the preferences are affected by framing. Notably, this remained true even when common payments were substantial (Study 2), and the framing effect was also found in scenarios where decisions carried real financial consequences (Study 3).
Keywords: 330; time preferences; framing; cancellation